STUDI KOMBINASI MEDIA TANAM DAN DEBIT AIR IRIGASI TETES PADA BUDIDAYA TANAMAN SELEDRI (Apium graveolens L.) - Anisa, Khairin; Junedi, Heri; Nizori, Addion (Jambi University, Fakultas Pertanian, Program Studi Agroekoteknologi, 2025)
Celery is a multipurpose plant with many health benefits that has not been widely developed, especially in Jambi. The problem is the lack of fertile land. This can be overcome by using planting media other than soil. The aim of this research is to obtain the best combination of planting media and drip irrigation water discharge for celery cultivation. This research was conducted in the Greenhouse of Penyengat Bawah Subdistrict in March-July 2023. The experimental design used a Completely Randomized Design (CRD) which was arranged in a factorial consisting of two factors. The first factor (planting media) consists of 5 levels which are a combination of a mixture of soil, areca nutshell biochar and swallow guano. The second factor is the water flow rate which consists of 3 levels, namely the flow rate of 2.8 ml/minute, 4.2 ml/minute, and 5.6 ml/minute with 2 repetitions. The parameters observed were analysis of the nutrient content of the planting medium, water content of the planting medium, plant height, number of leaves, and fresh weight of the plant. The results showed that the combination of planting media influenced all parameters. Providing water with different discharges affects the water content of the planting medium and the wet weight of celery plants but does not affect plant height, and number of leaves. The combination of soil planting media and areca nutshell biochar (1:2) with water supply of 5.6 ml/minute produces the best growth and results in the growth and production of celery plants (Apium graveolens L).